Albumin Use and Its Association with Nutritional Status in the Intensive Care Unit : A Narrative Review - Putu Eka Nantha Kusuma; Jeremy Jonathan; Putu Agus Surya Panji (Jurnal Anestesiologi dan Terapi Intensif, 2025)
Introduction: Albumin is the major protein in blood plasma that plays a pivotal role in the regulation of oncotic pressure and nutritional status, particularly in critically ill patients. Hypoalbuminemia is frequently observed in ICU patients and is associated with increased morbidity and mortality. This narrative review aims to assess the role and efficacy of albumin supplementation, administered both orally and intravenously, in supporting the nutritional status and prognosis of critically ill patients. Methods: A literature search was conducted across the PubMed, Google Scholar, ScienceDirect, and ProQuest databases utilizing the keywords: "albumin", "critical illness", "nutrition", and "ICU". Articles included were those published within the last 10 years, available in English and Indonesian, and comprised review articles, clinical trials, and clinical practice guidelines. The selection process was performed through the screening of titles, abstracts, and subsequent full-text reviews. A total of 23 articles were included in this review. Results: The literature indicates that albumin supplementation contributes to hemodynamic stability, a reduction in nosocomial infections, and improved prognosis in patients with conditions such as sepsis, ARDS, hepatic and renal dysfunction, and in post-operative states. Supplementation with snakehead fish (Channa striata) extract has also been reported to increase albumin levels. Accurate nutritional assessment, using tools like the Nutrition Focused Physical Exam (NFPE), Subjective Global Assessment (SGA), and biomarkers such as Total Lymphocyte Count (TLC) and Neutrophil to Lymphocyte Ratio (NLR) are essential for determining the nutritional status of critically ill patients. Specific recommendations from the ESPEN consensus and various hepatology and nephrology associations exist concerning the application of albumin in specific clinical conditions. Conclusion: Albumin supplementation holds significant potential in supporting the nutritional status and improving the clinical outcomes of critically ill patients. Further studies are required to determine optimal protocols and the cost-effectiveness of albumin therapy in the critically ill patient population.